The role of intelligence in enhancing learning motivation in the perspective of students of Charmo University in the College of Education - كریم, م.م.ئارام; بكر, م.م.ئیمان پشتیوان; محمد, م.م.عماد عبدالكریم; مراد, م.م.گوڵاڵه‌ صاڵح (Sulaimani Journal for Humanities, 2025)
The primary objective of this study is to identify and measure the role of artificial intelligence (AI) in developing and enhancing learning motivation from the perspective of students at the College of Education, Charmo University. The study population consisted of all students at the College of Education. A random sample of 92 students was selected from all departments and semesters for the academic year 2024-2025. Data were collected using a researcher-developed scale consisting of (26) positive and negative items. To ensure the validity of the instrument, it was reviewed by a panel of 11 experts in the fields of education and psychology. The reliability of the scale was determined to be 0.949. Data analysis was performed using the Statistical Package for the Social Sciences (SPSS, Version 26). The findings, in response to the study's hypotheses, revealed that artificial intelligence plays a significant role in developing and enhancing the learning motivation of college students in general. Regarding the gender variable, a slight statistical difference was observed between males and females, in favor of males. Furthermore, a notable difference was found among academic departments; students from the Department of English Language perceived the role of AI in elevating their learning motivation to be significantly more impactful. Conversely, students from the Department of Arabic Language perceived AI as having the least impact.
Keywords: Artificial Intelligence; Learning Motivation; University Students; Education; Perspectives